Generative design recommendations for the historical Mardiṅ High School and Gaziṗaşa Primary School buildings, Turkey - Mizgin Gökçe Salık; Fatma Demet Aykal (Conservation Science in Cultural Heritage, 2025)
The genetic algorithm (GA) is inspired by natural selection, emphasizing the survival of the fittest. In GAs, data is encoded as genes, and optimal solutions are achieved through crossover and mutation operations on these genes. This study focuses on a key issue in re-functionalizing buildings, where facade elements designed without sustainability concerns become problematic. The design approaches for interventions in historic buildings remain a point of debate in architectural conservation and restoration. This study examines the facade changes due to functional transformations in a historic educational building, using GA as a generative system approach. The research specifically suggests new door and window typologies suited to the functionalization process of traditional buildings in historical settings. Genetic algorithms and shape grammars were the main methods employed. A field study applied GA to propose new door and window types with compatibility values. The analysis focused on a historical high school in Mardin (Turkey), generating alternative joinery designs. Thirty window and fifteen door typologies were developed, and while the original building’s facade openings maintained their traditional form, some annex additions lacked conformity. It is thought that this study should be a methodology that can be used in the production of exterior joinery typologies in the additions or completions to be made in the process of re-functioning in many different cities, especially in the historical texture, to protect sustainability. It is believed that this approach will contribute significantly to conservation efforts in cultural heritage buildings, offering a reference for restoration practices.